Su Origene, Commento a Matteo 17, 1-3; 25-28 - Simonetti, Manlio (Augustinianum, 2014)
This comment concerns above all the existing relationship between the Greek text that has reached us and the ancient Latin translation of Origen’s Commentary on Matthew, analyzing two passages from the XVII book; that is, the interpretations of Mt. 21,23-27 and Mt. 22, 15-22. The Greek and Latin texts are not always consistent with one another: in most cases the Latin version abbreviates or omits some passages from the Greek, but at times it reveals typical exegetical minutiae from the origenian ratio interpretandi and absent from the incomplete Greek text available to us today, as the Author clearly points out in this study.